Research Progress of Rehabilitation Orthoses Based on 3D Printing Technology. (14th December 2022) - Li, Junqi; Chen, Shenggui; Shang, Xin; Li, Nan; Aiyiti, Wurikaixi; Gao, Fei
Abstract : Rehabilitation orthoses is currently a research hotspot in the field of 3D printing. Compared with traditional manufacturing methods, orthoses manufactured by 3D printing can meet the needs of patients in terms of structure and performance. This paper mainly introduces the research progress, main problems, and challenges of 3D printing rehabilitation orthoses in the medical field. At the same time, different 3D printing processes, types of medical materials, and contour extraction methods of the body surface area are compared. Its purpose is to provide a reference for the additive manufacturing of rehabilitation orthoses and their printing methods in medical research.